Simultaneous 3D whole‐heart bright‐blood and black blood imaging for cardiovascular anatomy and wall assessment with interleaved T2prep‐IR. Issue 1 (21st March 2019) - Milotta, Giorgia; Ginami, Giulia; Cruz, Gastao; Neji, Radhouene; Prieto, Claudia; Botnar, René M.
Abstract : Purpose: To develop a motion‐corrected 3D flow‐insensitive imaging approach interleaved T2 prepared‐inversion recovery (iT2 prep‐IR) for simultaneous lumen and wall visualization of the great thoracic vessels and cardiac structures. Methods: A 3D flow‐insensitive approach for simultaneous cardiovascular lumen and wall visualization (iT2 prep) has been previously proposed. This approach requires subject‐dependent weighted subtraction to completely null the arterial blood signal in the black‐blood volume. Here, we propose an (T2 prep‐IR) approach to improve wall visualization and remove need for weighted subtraction. The proposed sequence is based on the acquisition and direct subtraction of 2 interleaved 3D whole‐heart data sets acquired with and without T2 prep‐IR preparation. Image navigators are acquired before data acquisition to enable 2D translational and 3D non‐rigid motion correction allowing 100% respiratory scan efficiency. The proposed approach was evaluated in 10 healthy subjects and compared with the conventional 2D double inversion recovery (DIR) sequence and the 3D iT2 prep sequence. Additionally, 5 patients with congenital heart disease were acquired to test the clinical feasibility of the proposed approach. Results: The proposed iT2 prep‐IR sequence showed improved blood nulling compared to both DIR and iT2 prep techniques in terms of SNR (SNRblood = 6.9, 12.2, and 18.2, respectively) and contrast‐to‐noise‐ratio (CNRmyoc‐blood = 28.4, 15.4, and 15.3, respectively). No statistical difference was observed between iT2 prep‐IR, iT2 prep and DIR atrial and ventricular wall thickness quantification. Conclusion: The proposed interleaved T2 prep‐IR sequence enables the simultaneous lumen and wall visualization of cardiac structures and shows promising results in terms of SNR, CNR, and wall thickness measurement.